Mutational Studies of Putative Biosynthetic Genes for the Cyanobacterial Sunscreen Scytonemin in Nostoc punctiforme ATCC 29133 - Ferreira, Daniela; Garcia-Pichel, Ferran (Frontiers in Microbiology, 2016)
The heterocyclic indole-alkaloid scytonemin is a sunscreen found exclusively among cyanobacteria. An 18-gene cluster is responsible for scytonemin production in Nostoc punctiforme ATCC 29133. The upstream genes scyABCDEF in the cluster are proposed to be responsible for scytonemin biosynthesis from aromatic amino acid substrates. In vitro studies of ScyA, ScyB and ScyC proved that these enzymes indeed catalyze initial pathway reactions. Here we characterize the role of ScyD, ScyE and ScyF, which were logically predicted to be responsible for late biosynthetic steps, in the biological context of N. punctiforme. In-frame deletion mutants of each were constructed (∆scyD, ∆scyE and ∆scyF) and their phenotypes studied. Expectedly, ∆scyE presents a scytoneminless phenotype, but no accumulation of the predicted intermediaries. Surprisingly, ∆scyD retains scytonemin production, implying that it is not required for biosynthesis. Indeed, scyD presents an interesting evolutionary paradox: it likely originated in a duplication event from scyE, and unlike other genes in the operon, it has not been subjected to purifying selection. This would suggest that it is a pseudogene, and yet scyD is highly conserved in the scytonemin operon of cyanobacteria. ∆scyF also retains scytonemin production, albeit exhibiting a reduction of the production yield compared with the wild-type. This indicates that ScyF is not essential but may play an adjuvant role for scytonemin synthesis. Altogether, our findings suggest that these downstream genes are not responsible, as expected, for the late steps of scytonemin synthesis and we must look for those functions elsewhere. These findings are particularly important for biotechnological production of this sunscreen through heterologous expression of its genes in more tractable organisms.